THE DESCRIPTION OF EATING PATTERNS AND RISK FOR GASTRITIS IN STUDENTS AT A PRIVATE UNIVERSITY IN WESTERN INDONESIA - Eka Prasetyaningsih; Erol Pratama Duru; Ester Novitasari; Ineke Patrisia; Juwita Fransiska Surbakti (Nursing Current: Jurnal Keperawatan, 2021)
Gastritis is an acute or chronic inflammation that occurs in the gastric mucosa. According to WHO (2012), gastritis was ranked sixth of the top ten diseases that cause morbidity in the world. This study aims to identify an overview of eating patterns and the risk of gastritis occurrence in students at the Teacher College of Private University in the Western Indonesia. This research used descriptive quantitative with a cross-sectional approach. A sample of 165 students was taken using a purposive sampling technique. The research instrument used online questionnaires with univariate analysis. Result showed that there were 92 (55%) respondents who had irregular eating frequency, 94 (57%) respondents who had irregular meal times, 100 (60.6%) respondents who had irregular food types, and 101 respondents (61.2%) who were at risk of developing gastritis. Recommendations: The results of the study are expected to be used to provide education to respondents, families, and the community.